Does global health governance walk the talk? Gender representation in World Health Assemblies, 1948–2021. Issue 8 (23rd August 2022) - van Daalen, Kim Robin; Chowdhury, Maisoon; Dada, Sara; Khorsand, Parnian; El-Gamal, Salma; Kaidarova, Galiya; Jung, Laura; Othman, Razan; O'Leary, Charlotte Anne; Ashworth, Henry Charles; Socha, Anna; Olaniyan, Dolapo; et al.
Abstract : Background: While an estimated 70%–75% of the health workforce are women, this is not reflected in the leadership roles of most health organisations—including global decision-making bodies such as the World Health Assembly (WHA). Methods: We analysed gender representation in WHA delegations of Member States, Associate Members and Observers (country/territory), using data from 10 944 WHA delegations and 75 815 delegation members over 1948–2021. Delegates' information was extracted from WHO documentation. Likely gender was inferred based on prefixes, pronouns and other gendered language. A gender-to-name algorithm was used as a last resort (4.6%). Time series of 5-year rolling averages of the percentage of women across WHO region, income group and delegate roles are presented. We estimated (%) change ±SE of inferred women delegation members at the WHA per year, and estimated years±SE until gender parity from 2010 to 2019 across regions, income groups, delegate roles and countries. Correlations with these measures were assessed with countries' gender inequality index and two Worldwide Governance indicators. Results: While upwards trends could be observed in the percentage of women delegates over the past 74 years, men remained over-represented in most WHA delegations. Over 1948–2021, 82.9% of delegations were composed of a majority of men, and no WHA had more than 30% of women Chief Delegates (ranging from 0% to 30%). Wide variation in trends over time could be observed across different geographical regions, income groups and countries. Some countries may take over 100 years to reach gender parity in their WHA delegations, if current estimated trends continue. Conclusion: Despite commitments to gender equality in leadership, women remain gravely under-represented in global health governance. An intersectional approach to representation in global health governance, which prioritises equity in participation beyond gender, can enable transformative policymaking that fosters transparent, accountable and just health systems.